Early definite stent thrombosis with everolimus-eluting stents - Naito, Ryo (Clin Case Rep, 2015)
Stent thrombosis (ST) is a serious complication of percutaneous coronary intervention. Several factors are associated with ST, and combination of these factors increase the risk, even in everolimus-eluting stents, which have low risk of ST. We experienced a case of ST caused by limited coronary flow and resistance to antiplatelet agent.